Clinical characteristics and outcomes of COVID-19 patients with diabetes mellitus in Kuwait. Issue 4 (April 2021) - Alshukry, Abdullah; Bu Abbas, Mohammad; Ali, Yaseen; Alahmad, Barrak; Al-Shammari, Abdullah A.; Alhamar, Ghadeer; Abu-Farha, Mohammad; AbuBaker, Jehad; Devarajan, Sriraman; Dashti, Ali A.; Al-Mulla, Fahd; Ali, Hamad
Abstract: Background: COVID-19 has a highly variable clinical presentation, ranging from asymptomatic to severe respiratory symptoms and death. Diabetes seems to be one of the main comorbidities contributing to a worse COVID-19 outcome. Objective: In here we analyze the clinical characteristics and outcomes of diabetic COVID-19 patients Kuwait. Methods: In this single-center, retrospective study of 417 consecutive COVID-19 patients, we analyze and compare disease severity, outcome, associated complications, and clinical laboratory findings between diabetic and non-diabetic COVID-19 patients. Results: COVID-19 patients with diabetes had more ICU admission than non-diabetic COVID-19 patients (42.4% vs. 7.7%, p < 0.001). Diabetic COVID-19 patients also recorded higher mortality in comparison to non-diabetic COVID-19 patients (34.7% vs. 3.7%, p < 0.001). Diabetic COVID-19 patients had significantly higher prevalence of comorbidities, such as hypertension. Laboratory investigations also highlighted notably higher levels of C-reactive protein in diabetic COVID019 patients and lower estimated glomerular filtration rate. They also showed a higher incidence of complications. logistic regression analysis showed that every 1 mmol/L increase in fasting blood glucose in COVID-19 patients is associated with 1.52 (95% CI: 1.34–1.72, p < 0.001) times the odds of dying from COVID-19. Conclusion: Diabetes is a major contributor to worsening outcomes in COVID-19 patients. Understanding the pathophysiology underlining these findings could provide insight into better management and improved outcome of such cases. Abstract : COVID-19, Diabetes Mellitus, SARS-CoV2, inflammation, CRP, Glucose.